Предмет: Алгебра,
автор: markinmatvey1
упростите выражение (12 y-1)(y+2)-2y(6y-3)
Ответы
Автор ответа:
14
Решение:
(12у - 1) ·(у + 2) - 2у·(6у - 3) = 12у² + 24у - у - 2 - 12у² + 6у = (24у - у + 6у) - 2 = 29у - 2.
Ответ: 29у - 2.
(12у - 1) ·(у + 2) - 2у·(6у - 3) = 12у² + 24у - у - 2 - 12у² + 6у = (24у - у + 6у) - 2 = 29у - 2.
Ответ: 29у - 2.
Похожие вопросы
Предмет: Английский язык,
автор: ivankorobenkov957
Предмет: Химия,
автор: venomdaicer
Предмет: Алгебра,
автор: Gulgulowuo
Предмет: История,
автор: vlada235
Предмет: Алгебра,
автор: Аноним